Draft Annual Plan 1994-95 Vol. II (In 4 Volumes) Haryana State - Planning Commission (Planning Commission, 1994)
In broader terms there are three farming situations in the State 1. e. irrigated, semi irrigated and rain fed. Crops like Bajra in Kharif season & gram in Rabi season play a vital role in-increasing or decreasing the /agriculture-Production in the respective seasons. These crops generally are grown under rain fed & semi irrigated conditions. Ls regards, the area under sugarcane, it increases or decreases depending upon the timely disposal of the produce in the sugar mill and its price, The area under sugarcane has touched level of 1.62 lakh hectares during 1991-92 but it has decreased to about 1.34 lakh sheets during the year 1992-93. In fact, cane growers are not paid remunerative cane prices as compared to other competitive crops during last two crop seasons resulting a sharp decline in coverage under it. Moreover, the Sugarcane price is announced at the start of crushing season which does not help in covering more area under sugarcane at that time
Government of Haryana
Planning Department Government of Haryana
Keywords: Crop Husbandry; Storage and Warehousing; Agricultural Financial Institutions; Minor Irrigation; Soil and Water Conservation; Agricultural Research Education; Wild Life Preservation; Rural Development; Integrated Rural Development Programme; Drought Prone Area Programme; Consolidation of Holdings; Mewat Development Board; Shivalik Development Board